Impact of Employees Empowerment on Organizational Performance: A Study of Non-Government Organizations in Surkhet District - Kandel, Surya Prakash (Journal of Nepalese Management and Research, 2025)
The purpose of this study is to examine the influence of employee empowerment on organizational performance in non-government offices located in Surkhet District. Specifically, the study analyzes how organizational structure, leadership style, training and development, and reward systems affect overall organizational performance. The study adopts an explanatory research design and employs a causal-comparative research methodology. Data were collected from 201 employees working in non-government offices through a convenience sampling technique. Multiple regression analysis was applied to assess the impact of selected employee empowerment dimensions on organizational performance. SPSS software was subsequently used for data analysis, enabling the evaluation of the relationships between employee empowerment and organizational performance. The results indicate that leadership style has a strong and statistically significant positive impact on organizational performance (β = 0.526, p < 0.001), highlighting the central role of effective leadership in improving workplace efficiency and outcomes. Training and development (β = 0.048, p < 0.01) and reward systems (β = 0.155, p < 0.01) also show significant positive relationships with organizational performance, suggesting that investment in employee capability-building and incentive mechanisms contributes to improved performance. However, organizational structure (β = 0.048, p > 0.01) does not exhibit a statistically significant effect on organizational performance. The use of convenience sampling and the focus on non-government offices within a single district limit the generalizability of the findings. Nevertheless, the study provides practical implications for managers and policymakers by emphasizing the need to strengthen leadership practices, enhance training and development programs, and implement effective reward systems to foster employee empowerment and improve organizational performance. This study adds empirical value to the existing literature by providing district-level evidence on the role of employee empowerment in organizational performance. It highlights leadership style and reward systems as critical drivers of employee empowerment and institutional efficiency within the context of non-government organizations in Nepal.